What Drives Youth to Farm? Exploring Social, Economic, and Personal Factors - Sitompul, Thomson (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
Cross-regional survey studies found that determinants of factors consistently influence youth decisions to enter/stay in agriculture: land access, capital/financial access, education & technical training, and family/community support. By analyzing the literatures, regression analysis and mixed-methods studies generally show that without improved land access and financing, training programs alone are difficult to drive long-term retention. A number of Indonesian case studies (and reviews on agricultural digitalization) show that digitalization (marketing platforms, agronomic information, management systems) can increase the attractiveness of agriculture for younger generations and help them become agripreneurs—but the evidence on the medium-term economic impact (income, business stability) is still limited and most studies are descriptive or qualitative. There are reports that emphasize the great potential but also the obstacles to implementation (digital literacy, infrastructure investment).